Aesthetics of the Babuai Dance and the Transformation of Tradition at the Singo Barantai Traditional Arts Institute, Padang - Yosi Nofa; Yuliarni Yuliarni; Afrizal Harun; Asril Asril; Dede Pramayoza (LPPM Institut Seni Indonesia Padangpanjang, 2025)
Babuai dance is one of the traditional Minangkabau dances that developed at the Singo Barantai Padang Traditional Arts School. This dance is one of the unique traditional dances. Because the movements of this dance depict agility, softness, firmness and sharpness. In every movement is full of accents (movement jerks) besides that there is also acceleration and deceleration. This dance is used for body exercise for a silat athlete before they carry out silat training. The object of this research uses Dance as its formal object,